The Ten Hours Movement and the Working-Class Family in Mid-Nineteenth Century Britain. (2021) - Creighton, Colin
Abstract: The Ten Hours Movement of the 1830s and 1840s in Britain was the first large-scale working-class struggle to challenge the impact of industrial capitalism upon working-class family life. Yet its discourse on family has been relatively neglected by historians of the movement. This article examines the nature of the movement's critique, the vision of family life that it tried to realize, and the challenge that this posed to the emerging bourgeois order and, on this basis, to reconsider its contribution to the gender ordering of working-class family life.